Calling Hell from Heaven and Heaven from Hell - Peyton Jones, Simon; Meijer, Erik; Leijen, Daan; Finne, Sigbjörn (The International Conference on Functional Programming (ICFP'99), Paris, France, 1999)
The increasing popularity of component-based programming tools offer a big opporunity to designers of advanced programming languages, such as Haskell. If we can package our programs as COM objects, then it is easy to integrate them into applications written in other languages. In earlier work we described a preliminary integration of Haskell with Microsoft's Component Object Model (COM), focusing on how Haskell can create and invoke COM objects. This paper develops that work, concentrating on the mechanisms that support externally-callable Haskell functions, and the encapsulation of a Haskell program as a COM object.
Also appeared in ACM SIGPLAN Notices 34, 9, (Sep. 1999)